2021
DOI: 10.1021/acs.jmedchem.1c00561
|View full text |Cite
|
Sign up to set email alerts
|

Design of Negative and Positive Allosteric Modulators of the Cannabinoid CB2 Receptor Derived from the Natural Product Cannabidiol

Abstract: Cannabidiol (CBD), the second most abundant of the active compounds found in the Cannabis sativa plant, is of increasing interest because it is approved for human use and is neither euphorizing nor addictive. Here, we design and synthesize novel compounds taking into account that CBD is both a partial agonist, when it binds to the orthosteric site, and a negative allosteric modulator, when it binds to the allosteric site of the cannabinoid CB2 receptor. Molecular dynamic simulations and site-directed mutagenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 52 publications
3
42
0
Order By: Relevance
“…As would be expected from an allosteric mode of action, the binding of the compound to the allosteric site causes conformational changes in such a way that biases the effect of orthosteric agonists (Navarro et al, 2018a). A more recent report shows that structural changes in the molecule shifts negative to positive modulation (of the CB 2 R) thus confirming its allosteric nature (Navarro et al, 2021).…”
Section: Identification Of Non-orthosteric Sitesmentioning
confidence: 87%
See 2 more Smart Citations
“…As would be expected from an allosteric mode of action, the binding of the compound to the allosteric site causes conformational changes in such a way that biases the effect of orthosteric agonists (Navarro et al, 2018a). A more recent report shows that structural changes in the molecule shifts negative to positive modulation (of the CB 2 R) thus confirming its allosteric nature (Navarro et al, 2021).…”
Section: Identification Of Non-orthosteric Sitesmentioning
confidence: 87%
“…Thus, cannabidiol binds to an allosteric site at nanomolar concentrations while micromolar concentrations are required for significant binding to the orthosteric site. Accordingly, the in vitro results depend on the concentration while the in vivo actions at moderate doses should be mainly due to its binding to the allosteric site that has been very recently suggested to be close to the receptor entrance ( Navarro et al, 2021 ) (See section: “Structural Insights into CB 2 R Binding Modes”). As would be expected from an allosteric mode of action, the binding of the compound to the allosteric site causes conformational changes in such a way that biases the effect of orthosteric agonists ( Navarro et al, 2018a ).…”
Section: Orthosteric and Non-orthosteric Sites In The Cb 2 ...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, inhibiting CB2Rs with the antagonist AM630 would prevent the antipsychotic effects of M4 agonists. Preclinical studies also showed that cannabidiol (CBD), another major phytocannabinoid, which is devoid of intoxicating effects, has antipsychotic properties [92][93][94][95] mediated by the activation of CB2Rs [96][97][98]. It should be pointed out that CBD is a non-intoxicating rather than a non-psychoactive constituent in the cannabis plant.…”
Section: Schizophrenia and Cb2r-ecsmentioning
confidence: 99%
“…For instance, the main non-psychotropic component of Cannabis sativa, cannabidiol (CBD), is a CB2 partial agonist/TRPV1 agonist (De Petrocellis et al, 2011;Tham et al, 2018). It is worth mentioning that at CB2, CBD has been reported to act as negative allosteric modulator in the presence of orthosteric full agonists (Martínez-Pinilla et al, 2017;Navarro et al, 2021). The acidic CBD derivative, cannabidiolic acid (CBDA), and its propyl counterpart, cannabivarin (CBDV), also exhibited TRPV1 agonism while being CB2 partial agonists (De Petrocellis et al, 2011;Zagzoog et al, 2020).…”
Section: Structural Understanding Of Compounds With Reported Activity...mentioning
confidence: 99%